2004
DOI: 10.1271/bbb.68.1500
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Acylated Anthocyanins in Rats and Humans after Ingesting an Extract ofIpomoea batatasPurple Sweet Potato Tuber

Abstract: We evaluated the absorbability of anthocyanins in humans and rats administered with a beverage prepared from an extract of the tuber of purple sweet potato (Ipomoea batatas Cultivar Ayamurasaki), or with an anthocyanin concentrate. Two major anthocyanin components, cyanidin 3-O-(2-O-(6-O-(E)-caffeoyl-beta-D-glucopyranosyl)-beta-D-glucopyranoside)-5-O-beta-D-glucopyranoside) and peonidin 3-O-(2-O-(6-O-(E)-caffeoyl-beta-D-glucopyranosyl)-beta-D-glucopyranoside)-5-O-beta-D-glucopyranoside), were detected in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 28 publications
3
72
1
1
Order By: Relevance
“…, are selectively detected in the blood and rapidly excreted in the urine of rats and humans (Suda et al, 2002;Harada et al, 2004;Kano et al, 2005). The urinary recovery rate of PSP anthocyanins is very low (0.01% in humans and 0.11% in rats); however, the radical-scavenging activity in the urine is elevated after the ingestion of the PSP beverage (Kano et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, are selectively detected in the blood and rapidly excreted in the urine of rats and humans (Suda et al, 2002;Harada et al, 2004;Kano et al, 2005). The urinary recovery rate of PSP anthocyanins is very low (0.01% in humans and 0.11% in rats); however, the radical-scavenging activity in the urine is elevated after the ingestion of the PSP beverage (Kano et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the complex chemical structure of PSP anthocyanins, they are rapidly absorbed into the body, detected in blood and rapidly excreted in the urine of rats and humans (Suda et al, 2002;Harada et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…sop-5-glc content, 73 mg/125 ml). 7) In addition, there was no significant difference (p < 0:05) in the Pn 3-Caf . sop-5-glc concentration between men and women who ingested the same beverage (Student's t-test with logarithmic transformation of the data).…”
mentioning
confidence: 83%
“…Determination of Acylated Anthocyanin in Human Urinestudy. 7) The concentration ranged from 3.4 to 56.3 mg/l of urine in volunteers who ingested beverage A, from 13.8 to 147.4 mg/l of urine in those who ingested beverage B, and from 12.6 to 187.5 mg/l of urine in those who ingested beverage C. It was found that Pn 3-Caf . sop-5-glc was absorbed into the blood stream even though the anthocyanin content in the beverage was lower than that reported in a previous paper (Pn 3-Caf .…”
mentioning
confidence: 94%
See 1 more Smart Citation